Canção do Poeta do Século XVIII, de Heitor Villa-Lobos: identidade transitiva no repertório villalobiano para canto e violão (Orfeu, 2019)
With the gathering of data, premiere dates, interviews, first performances, recordings and critiques, as well as more than 30 unpublished articles in newspapers and periodicals, this article has two purposes: first, to make a genealogy of the three versions devised by Villa-Lobos for one of his still little known vocal pieces, the Song of an Eighteenth Century Poet; then, to assess whether the debate around aesthetic and/or stylistic issues was already present in the early records, performances and musical critiques that the work received throughout the 1960s and 1970s. The results raise a possible look at Villa-Lobos’s production for voice and guitar from the concept of “transitive identity” proposed by Llanos (2018).
Keywords: Heitor Villa-Lobos; Voice and guitar; Guitar and National Identity; Song of an Eighteenth Century Poet